2023
DOI: 10.1002/mdc3.13698
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Milestones Demonstrate Long Disability‐Free Survival in Parkinson's Disease Patients with Deep Brain Stimulation of the Subthalamic Nucleus

Abstract: Background Background: Deep brain stimulation of the subthalamic nucleus (STN-DBS) is an effective treatment for Parkinson's disease (PD). The long-term benefit in PD patients with STN-DBS in comparison to medical treatment (MT) alone has not yet been demonstrated conclusively. Objectives Objectives: To judge the long-term outcome of patients with STN-DBS. MethodsMethods: To assess the evolution of PD symptoms and health-related quality of life (HRQoL) after deep brain stimulation (DBS) surgery, we conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
(132 reference statements)
0
8
0
Order By: Relevance
“…Specifically, the occurrence of morbidity milestones, which include visual hallucinations, recurrent falls, the onset of dementia, and admission to a nursing facility, have been associated with poor prognosis heralding the final five years of the disease 13 . Even in patients with long-term deep brain stimulation (DBS), the same rapid progression was found after the onset of morbidity milestones—in spite of more benign disease trajectories in DBS patients in early to mid-stage disease 14 . These findings indicate a pathophysiological process, which is inherent to the last phase of the disease or an age-modulated exponential progression culminating in comparable trajectories.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically, the occurrence of morbidity milestones, which include visual hallucinations, recurrent falls, the onset of dementia, and admission to a nursing facility, have been associated with poor prognosis heralding the final five years of the disease 13 . Even in patients with long-term deep brain stimulation (DBS), the same rapid progression was found after the onset of morbidity milestones—in spite of more benign disease trajectories in DBS patients in early to mid-stage disease 14 . These findings indicate a pathophysiological process, which is inherent to the last phase of the disease or an age-modulated exponential progression culminating in comparable trajectories.…”
Section: Introductionmentioning
confidence: 98%
“…These findings indicate a pathophysiological process, which is inherent to the last phase of the disease or an age-modulated exponential progression culminating in comparable trajectories. Such an accelerated progression or “neurodegenerative storm” in the terminal stage can be illustrated in the form of a hockey-stick effect, which closes a steady linear deterioration with a steep upward curve at the end 13 , 14 . The underlying factors for these processes are unknown, however, both models could be caused by a failing stress compensation in already critically degenerated areas where only minor cellular loss acts as the straw breaking the camel’s back.…”
Section: Introductionmentioning
confidence: 99%
“…Such an accelerated progression or "neurodegenerative storm" in the terminal stage can be illustrated in the form of a hockey-stick effect, which closes a steady linear deterioration with a steep upward curve at the end. 14,15 The underlying factors for these processes are unknown, however, both models could be caused by a failing stress compensation in already critically degenerated areas where only minor cellular loss acts as the straw breaking the camel's back. Another possible mechanism is the spread of alphasynuclein beyond the midbrain structures, including the cortex and the limbic system, which results in a pronounced increase in the size of affected gray matter.…”
Section: Introductionmentioning
confidence: 99%
“…We thank Mahlknecht and colleagues for their thoughtful comments on our recently published research in which we examined the occurrence of disability milestones (frequent falls, hallucinations, dementia, and nursing home placement) and their relationship to death in a cohort of 162 patients with Parkinson's disease (PD) and deep brain stimulation of the subthalamic nucleus (STN-DBS). 1 In response to our work, they reanalyzed data from one of their previous studies comparing patients with deep brain stimulation (DBS) to a matched control group. 2 Similar to our observations, they found that psychosis was the only milestone to occur less frequently in patients with STN-DBS, which could be a consequence of the lower daily dose of dopaminergic medication.…”
mentioning
confidence: 99%
“…We thank Mahlknecht and colleagues for their thoughtful comments on our recently published research in which we examined the occurrence of disability milestones (frequent falls, hallucinations, dementia, and nursing home placement) and their relationship to death in a cohort of 162 patients with Parkinson's disease (PD) and deep brain stimulation of the subthalamic nucleus (STN‐DBS). 1 …”
mentioning
confidence: 99%